A gentle occupation : a novel - Bogarde, Dirk
In the uneasy aftermath of WWII, a group of ordinary British soldiers and their families find themselves stationed as peacekeepers at an outpost in the Java Sea. Whilst attempting to return the island to Dutch control, they are subject to violent attacks by the locals who want their freedom.